Individual and Family Protective Factors of Intentional and Unintentional Consumption of Online Pornography in Hong Kong - Lai, Catie C. W. (2016)
The purpose of the current study was to explore how positive youth development and family functioning were related to unintentional and intentional exposure to online pornography in Chinese adolescents. A total of 1401 secondary school students (mean age=12.43) participated in the study. Findings suggested that positive youth development and family functioning were associated with lower exposure to online pornography. In particular, higher levels of spirituality, social competence, mutuality and communication were associated with lower levels of both types of exposure to online pornography. Discussion focuses on the importance of promoting positive youth development and family functioning as protective factors against the negative influence of pornography among Chinese adolescents